Efficacy of 4-methyl-7-hydroxy coumarin derivatives against vectors aedes aegypti and culex quinquefasciatus - Deshmukh, Madhavi; Pawar, Pushpa; Joseph, Mary P.; Phalgune, Usha; Kashalkar, Rajashree; Deshpande, Nirmala R. (Indian Journal of Experimental Biology, 2008)
4-Methyl-7-hydroxy coumarin is considered as a lead molecule as a biopesticide. Its mono bromo and tribromo derivatives were synthesized. Two more derivatives were synthesized by acylation. Compound 1 (3.6,8-tribromo-7-hydroxy-4-methyl-chromen-2-one) was found to be the most potent against IV(th) instar larvae of C. quinquefasciatus and A. aegypti the LC(50) being 1.49 and 2.23 ppm respectively. It showed 100% larval mortality at 25 ppm against A. aegypti and at 10 ppm against C. quinquefasciatus. Compounds 1 and 2 (3,6,8-tribromo-7-hydroxy-4-methyl-chromen-2'-oxo-2H-chromen-7-yl acetate) showed remarkable ovicidal activity. Significant reduction of 80-85%, hatching of eggs of both mosquito species was observed at the highest dose of 100 ppm. The hatched larvae showed 100% mortality in the successive instars. Compounds 3 and 4 (3-bromo-7-hydroxy-4-methyl-chromen-2-one and 3-bromo-4-methyl-2'-oxo-2H-chromen-7-yl acetate) showed moderate activity against both mosquito species.
Keywords: 4-Methyl-7-hydroxy coumarin; Aedes aegypti; Culex quinquefasciatus; Larval mortality; Ovicidal activity

Susceptibility of aedes aegypti and culex quinquefasciatus larvae to gedunin-related limonoids - Gurulingappa, Hallur; Tare, Vrushali; Pawar, Pushpa; Tungikar, Vijay; Jorapur, Yogesh R.; Madhavi, Sriram; Bhat, Sujata V. (Chemistry & Biodiversity, 2009)
The major non-azadirachtin limonoids such as gedunin (1), epoxyazadiradione (3), nimbocinol (4), and nimolicinol (5) from Azadirachta indica A. Juss ('neem') and their derivatives were evaluated for their toxic action against fourth instar larvae of Aedes aegypti L. and Culex quinquefasciatus SAY. Gedunin exhibited 100% toxic action against both the mosquito larvae at 50 and 10 ppm. Epoxyazadiradione and epoxynimolicinol also showed significant toxicities (>= 50%) against larvae of both mosquito species at 50 ppm. These neem limonoids can have benefits in mosquito-control programs.